2013
DOI: 10.1177/1362480613497780
|View full text |Cite
|
Sign up to set email alerts
|

Neoliberal prisons and cognitive treatment: Calibrating the subjectivity of incarcerated young men to economic inequalities

Abstract: Based on fieldwork conducted in a cognitive-treatment setting for young men in jail, this article argues that contemporary rehabilitation efforts not only manifest theories of disciplinary and risk society, but also embody ideologies of the self and economic relations that are consistent with neoliberal capitalism. Drawing from Marxist theories of penality, we show that correctional officers seek to reconfigure the subjectivity of young incarcerated men in ways that adjust them to economic inequalities. For in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…The belief of YOT professionals in employability skills training as a solution to young people's employment difficulties echoes Kramer et al's. (2013) research in the USA which found that correctional officers unconsciously used these programmes to convey to young prisoners the neoliberal message that jobs were available if they actively took responsibility to seek them out.…”
mentioning
confidence: 95%
“…The belief of YOT professionals in employability skills training as a solution to young people's employment difficulties echoes Kramer et al's. (2013) research in the USA which found that correctional officers unconsciously used these programmes to convey to young prisoners the neoliberal message that jobs were available if they actively took responsibility to seek them out.…”
mentioning
confidence: 95%
“…In urging his parolees to “create doors for yourself,” Nelson communicates a belief that it is not structural inequalities that limit parolees’ opportunities to build better lives for themselves, but rather, it’s about “choices.” This is consistent with recent research on COs, many of whom are from communities and familial circumstances that are quite similar to those of the inmates they manage. Likewise, supervision workers can function as “the transmission points of broader ideologies that conceal fundamental inequalities” (Kramer, Rajah, and Sung 2013, 538; see also: Crawley 2004; Crewe 2011; Lerman and Page 2012; Liebling 2000).…”
Section: Resultsmentioning
confidence: 99%
“…This reveals a somewhat ambiguous understanding of the prisoners as both rational selves, capable of change but also as a cognitively disturbed self, and in some senses, essentially criminal (Fox 1999a; Rhodes 2010). Participation in the program can possibly enable the prisoners to alter their perceptions of being victims of disadvantaged circumstances and, consequently, their criminal actions (Kramer, Valli, and Hung 2013, 538; Sjöberg and Windfeldt 2008). However, Anger Management also strives to work within a social vacuum, where the prisoners are expected to decontextualize their acts of violence, rendering such actions entirely irrational and meaningless (cf.…”
Section: Contextualized Violencementioning
confidence: 99%